Benefits of Substance Use Disorder Screening on Employment Outcomes in State–Federal Vocational Rehabilitation Programs. (April 2014) - Heinemann, Allen W.; Moore, Dennis; Lazowski, Linda E.; Huber, Mary; Semik, Patrick
We evaluated benefits of substance use disorder (SUD) screening on employment outcomes of state vocational rehabilitation (VR) consumers in Illinois, Ohio, West Virginia, Kentucky, and Utah. Across states, 9, 681 screeners matched RSA-911 records with closure status. Positive SUD screening rates ranged from 21.2% in Illinois to 50.4% in Utah. While findings varied by state, screening can improve successful employment rates. Systemwide SUD screening may be most beneficial in states that are effective in addressing SUD. Effective states serve a higher percentage of consumers with SUD diagnoses, and have employment rates that meet or exceed states with fewer consumers with SUD, indicating that SUD success rates approximate those of consumers with other disabilities. Even in states with low SUD diagnoses rates, above 20% of screened consumers had suspected SUD. We replicated findings suggesting that persons with SUD can transition successfully to employment, and at lower cost and shorter time than consumers with other conditions. We found discrepancies in all states between SUD screening results and official diagnoses. Persons with a diagnosis of SUD were somewhat more likely to achieve an employment outcome than persons who screened SUD positive without a diagnosis. We provide suggestions for VR policy and future research directions.